[Dudley, Matthew (actor) : programs and related material collected by the National Library of Australia]
Material in the Australian performing arts programs and ephemera (PROMPT) collection consists of programs and related items for Australian performing arts organisations, Australian artists performing overseas, professional productions performed in Australia (including those featuring overseas performers) and overseas performances of Australian plays, music, etc.
Matthew Dudley is an actor who was born in Fremantle, Western Australia, and trained at Murdoch University, the Manchester Metropolitan University School Of Theatre and at The Desmond Jone School of Mime and Physical Theatre. He has appeared in West End Theatre, national touring productions, commercials, corporate work and pantomimes. [Information from his profile on https://actors.mandy.com/uk, 2018.]
This collection is featured in the Guide to Australian Performing Arts Programs and Ephemera (PROMPT) Collections in the National Library of Australia
Keywords: Dudley, Matthew -- Miscellanea; Actors -- Western Australia -- Miscellanea; Theater programs -- Australia; Performing arts -- Australia; Printed ephemera -- Australia; Australian